Human foamy virus genome possesses an internal, Bel-1-dependent and functional promoter. - Löchelt, M (1993)
The human foamy or spumaretrovirus (HSRV) is a complex retrovirus that encodes the three retroviral genes gag, pol, and env and, in addition, at least three bel genes. The HSRV Bel-1 protein was identified as a transcriptional trans-activator. HSRV transcription starts in the 5' long terminal repeat at a defined guanine residue. We report here that a second efficiently utilized start site of transcription is contained within a HSRV env DNA sequence upstream of the bel genes. Bel-specific transcripts that initiate at the internal transcriptional start site at nt 9196 were identified in HSRV-infected cells by primer extension and S1 nuclease analysis, and the intragenic promoter was shown to be constitutively activated by Bel-1 in the HSRV provirus. In transient expression assays with indicator gene constructs, expression by the HSRV intragenic promoter/enhancer is Bel-1 dependent. The data provide evidence for an intragenic start site of transcription in the genome of a complex, exogenous human retrovirus and are discussed in terms of a model for regulating spumaretroviral gene expression.